Expanding the Frontiers of Learning in Educational Institutions: An Approach towards Challenges Faced by Leaders and Followers - Ali, Azham, Md. (Modern Perspectives in Language, Literature and Education Vol. 10, 2021)
In expanding – nay, breaking – the frontiers of learning in educational institutions, internet is the answer. Indeed, there is now a new mode of learning and teaching with Web 2.0 tools. At the same time, there is the multitude of challenges faced by those with interest in integrating technology with the classroom learning experience. Technology has always helped enhance the simplest of tasks, such as the advancement of the traditional learning process. The challenges of concern are internet access, teachers’ education, teachers/lecturers modeling for the students, new additional skills or literacies and alternative paths in integrating technology with the classroom experience. It seems that to ensure smooth integration of technology in the classroom, the collaborative or shared leadership style appears to be the most appropriate for those concerned.